2020
DOI: 10.4103/ijd.ijd_291_20
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vitiligo: A subset of vitiligo

Abstract: Chemical leucoderma, an under-diagnosed common condition often mimicking idiopathic vitiligo, represents an acquired depigmentation induced by repeated exposure to specific chemical compounds in subjects with genetic susceptibility to vitiligo. This has been increasing rapidly in incidence in recent decades in developing countries like India. The term 'chemical vitiligo' was first coined by us to indicate the possible relationship between chemical leucoderma and vitiligo, which has been supported recently by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recent reports have shown that epidermal cytokine imbalance plays an important role in the induction of hypomelanotic lesion formation. A significant increase in the expression of inflammatory cytokines, such as IL6, TNF-α, IFN-γ, or IL2, and ET-1 or SCF expression reduction show melanocyte-stimulating activity [9,[18][19][20]. Recently, an outbreak of RDIL occurred in Japan, resulting in social impact and interest in the precise analysis of the pathogenesis and development of effective treatments for similar refractory vitiligo [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that epidermal cytokine imbalance plays an important role in the induction of hypomelanotic lesion formation. A significant increase in the expression of inflammatory cytokines, such as IL6, TNF-α, IFN-γ, or IL2, and ET-1 or SCF expression reduction show melanocyte-stimulating activity [9,[18][19][20]. Recently, an outbreak of RDIL occurred in Japan, resulting in social impact and interest in the precise analysis of the pathogenesis and development of effective treatments for similar refractory vitiligo [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was found that some commonly used daily necessities, such as disinfectants, diaper creams, cosmetic dyes, etc., can also cause skin discolorations. These chemically-induced depigmented spots were named "chemical vitiligo" by Ghosh, which is defined as acquired depigmentation caused by repeated exposure to a specific compound in genetically susceptible individuals, which is similar to idiopathic vitiligo [2].…”
Section: Chemical Vitiligomentioning
confidence: 99%
“…Several experimental evidences have shown that melanocytotoxic chemicals, especially phenolic and catechol derivatives, could cause vitiligo [ 4–7 ]. To our knowledge, few epidemiological studies are available on vitiligo induction factors and particularly on the role of exposure to chemicals in the onset of the disease has been found [ 8 ]. Therefore, there is a need to investigate the relationship between vitiligo and chemical exposures in order to understand this mysterious disease.…”
Section: Introductionmentioning
confidence: 99%